Do the barriers of multi-tier sustainable supply chain interact? A multi-sector examination using resource-based theory and resource-dependence theory. Issue 5 (December 2021) - Chand, Pushpendu; Tarei, Pradeep Kumar
Abstract: In a geographically dispersed multi-tiered supply chain, managing sustainable practices throughout the entire upstream network is increasingly challenging for the lead firm. But often, it is the lead firm that is held responsible for the lack of non-sustainable practices by any of its suppliers in the network. This can potentially damage the reputation of the lead firm. Moreover, complex inter-relationship among multi-tier sustainable supply chain management (MSSCM) barriers tends to constrain the cascading of sustainability. Consequently, the strategies in overcoming the MSSCM barriers show limited impact. Thus, exploring the mutual interaction among MSSCM barriers is crucial as removing one barrier can intensify or diminish the effect of another barrier. This research unpacks the intra-firm, inter-firm, and contingency barriers for multi-tiered supplier network. A grey-based multi-criterion decision-making approach is adopted in establishing mutual relationships among MSSCM barriers. In addition, a combined resource-based theory and resource-dependence theory supports the theoretical anchoring. The MSSCM barriers are studied for supply networks which involve three lead firms, five tier-one suppliers, and ten lower-tier suppliers selected from automobile, beverage, and home appliances industries. The research provides a granularity of the MSSCM barriers' by analysing the meaningful relationship at the individual tier-firm level and aggregated level. Highlights: - The study provides causal-prominence inter-relationship among multi-tier sustainable supply chain management (MSSCM) barriers. - It enhances granularity of the MSSCM barriers' by analyzing the influential relationship at the individual tier level and aggregated firm level. - Research outcome offers multi-industry cross-case analysis to provide generalization of the outcome across sectors and tiers. - Provides practical implication for managerial decision-making and policy formulation supportive of overcoming MSSCM barriers